Study of traditional fish drying activities at Atrai upazilla of Naogaon district in Bangladesh - Dey, Shishir Kumar; Hossain, Md Rayhan; Flowra, Fawzia Adib; Sultana, Sayeeda; Akter, Rubia (Asian Journal of Medical and Biological Research, 2017)
The investigation was conducted on traditional fish drying activities of the Atrai upazila under Naogaon district from July 2011 to December 2011. There was only one fish drying point was found in study area. The observed fish drying points are seasonal (from July to December). There are sixteen fish species were identified for drying among study area. Most of the raw fish collect from local market or Atria River. Transportation of raw fish was done by non-mechanized van or by head load of the labour. Price of the raw fish varied according to the species, size and availability. It is observed that September-October peak period for drying. The rate of mixing salt in the study area was found as 1kg salt for 12 kg of raw fish. At normal weather condition drying duration recorded to be varied from 2-5 days depend on the size of the raw fish. Plastic, jute sack and sometimes bamboo baskets were used for packaging purpose. The marketing channel is too small here. It was found that all the dried fish product in study areas, carried to the Sayadpur dry fish wholesale market in Nilphamary district directly by producers. The annual production of dried fish range 6000-8000 Kg. The highest price per kg dried fish was found as 400-550 Tk (Baim) and the lowest was found as 90-120 Tk (Punti, Darkina, Colisa). The cost benefit ratio for fish drying activities of study area was 1:0.671. The dry fish trader faced some problem such as insufficient credit, lack of raw fish insect infestation, storage and marketing facilities. From the present study some recommendations were also formulated to minimize the problem. Asian J. Med. Biol. Res. December 2016, 2(4): 646-655